2011
DOI: 10.4187/respcare.00981
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Current Intensive Care Unit Ventilators During Pressure and Volume Ventilation

Abstract: During VA/C, tidal volume was set at 500 mL and inspiratory time was set at 0.8 second. Rise time and termination criteria were set at the manufacturers' defaults, and to an optimal level during PS and PA/C. RESULTS: There were marked differences in ventilator performance in all 3 modes. VA/C had the greatest difficulty meeting lung model demand and the greatest variability across all tested scenarios and ventilators. From high to low inspiratory muscle effort, pressure-to-trigger, time for pressure to return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Such information suggests that one ventilator may not suit all patients, nor may one ventilator provide optimal ventilation in individual patients as their clinical status changes and underlines the importance of regular clinical evaluation [21].…”
Section: Physiological Variablesmentioning
confidence: 98%
“…Such information suggests that one ventilator may not suit all patients, nor may one ventilator provide optimal ventilation in individual patients as their clinical status changes and underlines the importance of regular clinical evaluation [21].…”
Section: Physiological Variablesmentioning
confidence: 98%
“…Many artificial lungs are able to simulate the entire respiratory system of an adult, allowing the setting of essential respiratory characteristics (lung compliance, airway resistance, etc). While the evaluation of some airway equipment can be carried out on a lung simulator alone , most studies connect it to a manikin to model the face and airways . Evaluation of the characteristics of the manikin is rarely undertaken, and to our knowledge, nobody has studied its impact on the data collected.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of a turbine is that it means the ventilator can operate without high-pressure compressed air. The potential limitations of a turbine include the risk of the gas reaching a high temperature at the ventilator outlet, the lack of accuracy in F I O 2 when the oxygen is added, and the lack of accuracy V T delivery for patients with a marked impairment in respiratory mechanics (6). A previous bench study demonstrated acceptable temperatures at the outlets of turbine ventilators, and hence a very low risk of humidifier dysfunction (7).…”
Section: Problems Of F I O 2 and Tidal Volume (V T ) Use And Indicatmentioning
confidence: 99%